Pendampingan Masyarakat Candi dalam Budidaya Tanaman Sawi dengan Metode Hidroponik di Kabupaten Sidoarjo - Vera Rimbawani (LPPM Universitas Yudharta Pasuruan, 2020)
The Brassica Juncea L cultivation using the hydroponic method was chosen as one of the programs for the community. Cultivation of Brassica Juncea L plants by hydroponics to get to know plants that are better without using soil and fertilizer and to save more land in the village of Sidoarjo temple. Assistance is done is to make the planting media and then socialize how to cultivate it and the obstacles that may arise and the solution to the community. The results of this assistance are expected by the community to be able to continue and develop this program ffter being left by a team of community service, so that it can benefit the community, at least to utilize vacant land and meet the needs of vegetables for the household, and if abundant harvests can be sold and eventually bought improve the economy of the community.